Global impact of the Antarctic ozone hole: Dynamical dilution with a three-dimensional chemical transport model - Prather, Michael; Garcia, Maria M; Suozzo, Robert; Rind, David (Journal of Geophysical Research, 1990)
A study of the Antarctic ozone hole has been made with a three-dimensional chemical transport model (CTM) using a linearized photochemistry for ozone. The tracer model uses the winds and convection from the Goddard Institute for Space Studies general circulation model (8° × 10° × 23 layers). The general circulation model (GCM) develops an Antarctic circumpolar vortex in early winter with strong westerlies that reverse in austral spring; the circulation compares favorably with the observed climatologies. A 4-year control run of the CTM with annually repeating winds produces ozone distributions that compare reasonably with the observed climatology. We examine different linearizations of the ozone chemistry and show that the calculated column ozone is sensitive to the chemical time constants in the lower stratosphere. In separate numerical experiments a hypothetical Antarctic ozone “hole” is induced on September 1 and on October 1; the CTM is integrated for 1 year with a linearized model that assumes standard photochemistry, not including the heterogeneous reactions and unusual chemistry associated with formation of the ozone hole. The initial depletion, assumed to be 90% of the O3poleward of 70°S between 22 and 200 mbar, amounts to about 5% of the total O3 in the southern hemisphere. As the vortex breaks down and the ozone hole is dispersed, significant depletions to column ozone, of order 10 Dobson units (3%) occur as far north as 40°S during austral summer. One year later, only 30% of the original depletion remains, mostly below 100 mbar and poleward of 30°S. The October 1 initialization is continued for a second year, the ozone hole being reinduced 1 year later with the same parameterization. The cumulative effects from the year before are noticeable but add only 20% to the depletion. A budget analysis for the southern high-latitude stratosphere (10–350 mbar × 31°–90°S) indicates the ozone hole is replenished equally by photochemical regeneration and by reduced transport of ozone into the troposphere, with a lesser fraction being filled in by an increased flux from the tropical stratosphere.